Identity through two lenses: the Slovak minority’s self and external views in Poland - Bryja, Marek (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the ethnic identity of the Slovak minority in Poland, focusing on their self-identification and external perceptions. It explores the fluid and dynamic nature of ethnic identity, drawing on theoretical perspectives from scholars such as Babiński and Isajiw. The historical context is analysed, tracing the Slovak minority’s presence in Poland to economic migrations before 1918. Employing a diagnostic survey method, the research investigates the perceptions of both Slovaks and Poles, offering a comparative analysis. The findings suggest that the core elements of the Slovak minority’s identity are rooted in language, traditions, culture, and religion. Despite successful integration and generally positive recognition in Polish society, certain stereotypes and biases persist. The study highlights the dual nature of this identity, where acceptance is accompanied by lingering cultural misconceptions. The research emphasizes the critical role of media and educational institutions in promoting tolerance and understanding of ethnic minorities. It advocates for more active involvement of these institutions in fostering inclusivity and shaping public attitudes, thereby contributing to developing a more culturally diverse and cohesive society in Poland.